Hiperglicemia materna: efeitos no cuidado materno e no desenvolvimento e comportamento dos descendentes - Kiss, Ana Carolina Inhasz [UNESP] (2011)
The aim of the present study was to evaluate the effect of maternal mild hyperglycemia on maternal behavior, as well as on offspring development, behavior, reproductive function, and development of glucose intolerance in adulthood. At birth, litters were assigned either to Control (subcutaneous(sc)- citrate buffer) or STZ group (streptozotocin(STZ)-100mg/kg-sc.). On PND 90 rats were mated. Glucose tolerance test (GTT) and insulin tolerance test (ITT) were performed during pregnancy. Pregnancy duration, litter size and sex ratio were assessed. Newborns were classified according to birth weight as small (SPA), adequate (APA), or large for pregnancy age (LPA). Maternal behavior was analyzed on PND 5 and 10. Offspring physical and sexual development was evaluated. Offspring body weight, length, and anogenital distance was measured and general activity was assessed on open field. Sexual behavior studies were conducted on both male and female offspring. Levels of reproductive hormones and estrous cycle duration were evaluated in female offspring. Female offspring were mated and GTT and ITT performed during pregnancy. STZ neonatal administration caused mild hyperglcyemia during pregnancy and changed some aspects of maternal care. The hyperglycemic intrauterine millieu impaired physical development and increased imobility on the open field in the offspring although the latter effect appeared at different ages for males (adulthood) and females (infancy). However, offspring sexual behavior was not impaired and, during pregnancy, STZ female offspring did not become glucose intolerant. Therefore, it can be concluded that mild hyperglycemia during pregnancy caused changes in maternal behavior, as well as offspring development and general activity, but failed to induce glucose... (Complete abstract click electronic access below)